Continuum level density calculated under the absorbing boundary condition. (8th December 2022) - Maeda, T; Taniguchi, Y; Fumimoto, T; Nakamoto, R; Ito, M
Abstract: We have applied an absorbing boundary condition (ABC) method to calculations of the level density (LD) and the continuum level density (CLD). The results of LD and CLD in the ABC calculation are compared with those calculated by the complex scaling method (CSM). The energy dependences of LD in ABC show similar behavior to those in CSM around the resonance energy but they are prominently different, especially at the lower-energy region, due to the different sequence of the energy eigenvalues in the complex plane. The phase shift for two-body scattering problems is also derived from CLD. The phase shift obtained by ABC is almost the same as that calculated from CSM although the ABC method seems to be slightly inferior to the CSM calculation in the numerical precision. The improvement of the numerical precision in ABC is also discussed.